Pattern of Surgical Antibiotic Prophylaxis in a Tertiary Care Hospital of Bangladesh (East West Medical College Journal, 2024)
Background: Surgical Site Infection (SSI) is a common form of hospital-acquired infection and major cause of postoperative illness accounting for approximately a quarter of all nosocomial infections. As a result, surgical antibiotic prophylaxis is now considered essential to conventional surgical procedure in order to reduce surgical site infections and improve postoperative recovery. The misuse and overuse of antibiotics has led to an increase in treatment costs and the emergence of antimicrobial resistance. The goal of the study is to identify the pattern of prophylactic antibiotic prescriptions for different surgical operations. Materials and methods: A retrospective observational study was conducted among 600 patients undergoing different surgeries in a tertiary care hospital of private setting in Dhaka, Bangladesh from July 2023 to December 2023. The demographic data, types of surgery, types of therapy, choice of antibiotic along with dosage formulations were collected. Results: Out of 600 patients, 245 (41%) were male and 355 (59%) were female. Highest bulk of patients were from Department of General Surgery (47.5%), followed by Department of Obstetrics & Gynecology (24.16%) and Department of Otolaryngology (16.7%). Surgical prophylactic antibiotic was used in all 600 patients, and all antibiotics were given in intravenous route (100%). Almost 505 patients (84.2%) had received ceftriaxone as antimicrobial agent. Ceftriaxone with metronidazole or gentamicin and Cefuroxime with metronidazole or amikacin drugs combination were given to 75 (12.5%) and Cefuroxime, Amikacin, Metronidazole drugs combination were given to 20 patients (3.3%). 3rd generation cephalosporin, Ceftriaxone, was the most commonly prescribed antibiotic as monotherapy (94.3%), followed by 2nd generation cephalosporin, cefuroxime (4%). Conclusion: Ceftriaxone was the preferred antibiotic for surgical prophylaxis. Existence of an antimicrobial guideline along with antibiotic stewardship program in every hospital could be helpful for prescribers to play role in containment of antimicrobial resistance.EWMCJ Vol. 12, No. 1&2, January-July 2024: 70-74